Desempenho de motor Ciclo diesel em bancada dinamométrica utilizando Biodiesel etílico de soja - Castellanelli, Márcio (2006)
Ahead of the forecast of scarcity of the oil, the ethyl ester (biodiesel) if has presented as an excellent alternative fuel option for engines cycle diesel. The characteristics of biodiesel are similar of diesel in terms of viscosity and the calorific power, being able to be used without adaptations in the engines. For accomplishment of this work, a motor cycle was used diesel, of direct injection with four cylinders, without adaptations. The engine was connected to a dynamometer and systems of acquisition of data auxiliary for the register of the necessary data. The performances of torque, power and brake specific fuel consumption for the following mixtures had been evaluated: B2, B5, B10, B20, B50, B75 and B100. The best registered performance was given with the B20 mixture.